A method of calculating water and soil loading on top of shallow shield tunnels near water areas - Zhu, Zeqi; Chang, Liuming; Cui, Lan; Sheng, Qian (Frontiers in Earth Science, 2023)
Long-term water seepage in shield tunnels has a serious impact on water and soil loading on the outer surfaces of a shield segment. A theoretical analysis was used to obtain a formula to express the average vertical seepage gradient at the top of the tunnel. A formula for calculating the coefficient of lateral earth pressure for the principal stress arch effect was utilized. A model that takes into consideration the effects of long-term water seepage on the shield tunnel’s water and soil load was designed. Based on the geological conditions and field survey results of water and soil loading of two typical segments of the Maliuzhou Waterway section of the Hengqin Tunnel, a comparative analysis of the theoretical results and field survey measurements was performed for different calculated conditions. The following primary conclusions were obtained: the proposed model is able to perform a reasonably effective evaluation of the water and soil pressure at the top of the shield tunnel for the marine and land segments of the shield tunnel; and, when compared with Dimitrios Kolymbas’ effective stress method and Terzaghi’s Principle, the method shown in this paper has fewer errors. As the angle of internal friction of a body of soil increases, the coefficient of lateral earth pressure will first decrease slightly and then increase, showing that the soil arching effect will only be a driving influence on the coefficient of lateral earth pressure under certain conditions. The soil and water load on the top of the tunnel have a positive correlation to the tunnel depth-to-diameter ratio with a rate of increase that gradually drops off. The soil and water load on the top of the tunnel has a positive linear correlation with the density of the body of soil and the water head on the outer section. The soil and water load on the top of the tunnel has a negative linear correlation with the amount of water seepage per unit length. The results of the associated research are sufficient to reasonably design and propose a theoretical basis for underwater shield tunnels in China.